KOMPARASI PREFERENSI PETANI JAGUNG DAN CABAI RAWIT DALAM MATERI PENYULUHAN UNTUK PERTANIAN BERKELANJUTAN - Anisa, Anisa; Arsyad, Karlena; Sirajuddin, Zulham (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Suwawa Selatan is one of the areas vulnerable to climate change, this condition is caused by unsustainable agricultural practices such as land clearing on slopes and burning agricultural waste. This study aims to identify the level of knowledge and implementation of sustainable agriculture that is relevant to the needs of farmers and prioritize extension materials needed by farmers. The method used in this study is a quantitative method that uses BNA analysis techniques and independent T-test statistical tests. The results showed that maize farmers had a lower knowledge level than chili farmers regarding sustainable agriculture components. Meanwhile, chili farmers in Suwawa Selatan needed more materials to increase the use of organic fertilizers and reducing excessive soil plowing (priority), while the priority extension materials for corn farmers in Suwawa Selatan sub-district were reducing the use of chemical fertilizers and reducing the use of chemical herbicides (priority).